(3CSGSjGJ GdJShjb (B/s - (3chJdQ, ajdjHs; (3CQeSJQhfL, LGQj s ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 1998)
(3QjGVjGJ GdJShjb, GdYed GdhXjaj aj GdJShjb, JSYjQ GdefJLGJ, bfhGJ GdJShjb hSdhc GdeTJQj, JLGQI GdJLRFI hJLGQI GdLedI, CShGb GdCYeGd, GSJQGJjLjI GdJShjb hJMOjO GdehbY, HfGA GdYdGbGJ GdUMjMI eY GdYedGA GdUMMjf, GSJQGJjLjGJ GdefJL hGdNOeGJ hGdYdGbI GdJLGQjIs
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs